Limb Regeneration in Axolotl: Is It Superhealing?. (2006) - Roy, Stéphane; Lévesque, Mathieu
Abstract : The ability of axolotls to regenerate their limbs is almost legendary. In fact, urodeles such as the axolotl are the only vertebrates that can regenerate multiple structures like their limbs, jaws, tail, spinal cord, and skin (the list goes on) throughout their lives. It is therefore surprising to realize, although we have known of their regenerative potential for over 200 years, how little we understand the mechanisms behind this achievement of adult tissue morphogenesis. Many observations can be drawn between regeneration and other disciplines such as development and wound healing. In this review, we present new developments in functional analysis that will help to address the role of specific genes during the process of regeneration. We also present an analysis of the resemblance between wound healing and regeneration, and discuss whether axolotls are superhealers. A better understanding of these animals' regenerative capacity could lead to major benefits by providing regenerative medicine with directions on how to develop therapeutic approaches leading to regeneration in humans.